Your boss is not your mother eight steps to eliminating office drama and creating positive relationships at work - Mandel, Debra; ebrary, Inc. (Chicago [Ill.] : Agate, 2006)
"A business woman's guide to creating and maintaining positive relationships in the workplace"--Provided by publisher.
"An AgatePro book"--P. [4] cover.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Organizational behavior; Transference (Psychology); Emotional maturity; Interpersonal relations; Work -- Psychological aspects; Electronic books